Improvement in Productivity of Wheat with Crop Residue and Nitrogen -A Review - Singh, Avtar; Kaushal, Meenakshi; Singh, Harmeet (Asian Journal of Biological and Life Sciences, 2012)
Wheat (Triticum aestivum L.) is the world's number one cereal crop in all the six continents of the world. It is the staple food of billions of people and is widely treated as cash crop because it produce good yield per unit area in short growing season. In world, wheat was grown on 225.6 million hectare with a production of 685.6 million tons and average productivity was 3039 kg/ha-1 during 2009-10. In India, the area under wheat was 28.25 million hectare and production was 80.7 million tons with productivity 2839 kg/ha-1 during 2009-10. In Punjab area, production and productivity under wheat was 3.5 million hectare, 15.2 million tons and 4307 kg/ha-1 during 2009-10, respectively.